Inside the Pot House: Diaspora, Identity, and Locale in Barbadian Ceramics. (1st November 2013) - Finch, Jonathan
<x xml:space="preserve">Abstract</x> A debate about the role of ceramics in communicating social identities among enslaved Africans has been a primary element of archaeological investigations of African diasporas. Early studies sought to identify distinct production techniques and vessel forms among low-fired earthenwares that were made on and traded between plantations and relate those to particular pottery types produced in regions of Africa impacted by the trans-Atlantic slave trade. A theoretical shift occasioned by contextual archaeologies refocuses attention on how artifacts and spaces were used by enslaved workers to forge identities through the social and labor relationships that surrounded them. This article investigates the production of earthenware on Barbados during the eighteenth century, where production techniques and vessel forms did not conform to early archaeological models of Africanisms and cultural markers. This study employs documentary evidence to explore the locales within which pottery was produced on a group of related plantations. Drawing on work by Silliman and Gosselain, this article argues that a combination of ethnic and demographic evidence from particular pottery production locations can illuminate how new African diaspora social identities were negotiated and communicated within and between enslaved communities during the working tasks of the plantations.